2004
DOI: 10.1128/jb.186.14.4596-4604.2004
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Anaerobic Survival of the Opportunistic Pathogen Pseudomonas aeruginosa via Pyruvate Fermentation

Abstract: Denitrification and arginine fermentation are central metabolic processes performed by the opportunistic pathogen Pseudomonas aeruginosa during biofilm formation and infection of lungs of patients with cystic fibrosis. Genome-wide searches for additional components of the anaerobic metabolism identified potential genes for pyruvate-metabolizing NADH-dependent lactate dehydrogenase (ldhA), phosphotransacetylase (pta), and acetate kinase (ackA). While pyruvate fermentation alone does not sustain significant anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
252
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(264 citation statements)
references
References 44 publications
7
252
4
1
Order By: Relevance
“…Fermentation is an important mechanism for anaerobic growth of bacteria in the absence of alternative electron acceptors (22), and several genes of typical pyruvate fermentation pathways were found such as pta (GT3361), ackA (GT2688), ldh (GT0487), and buk (GT2309). The por genes (GT1718-GT1717), which encode pyruvate-ferredoxin oxidoreductase and are commonly present in anaerobic bacteria (23), were also found.…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation is an important mechanism for anaerobic growth of bacteria in the absence of alternative electron acceptors (22), and several genes of typical pyruvate fermentation pathways were found such as pta (GT3361), ackA (GT2688), ldh (GT0487), and buk (GT2309). The por genes (GT1718-GT1717), which encode pyruvate-ferredoxin oxidoreductase and are commonly present in anaerobic bacteria (23), were also found.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, arginine sustains moderate anaerobic growth via fermentation (44). Recently, we have shown that pyruvate-one of the most abundant metabolites in all cells-allows anaerobic long-term survival of P. aeruginosa (13). However, in contrast to denitrification and arginine fermentation, pyruvate fermentation does not sustain anaerobic growth.…”
mentioning
confidence: 99%
“…We identified three enzymes essential for pyruvate fermentation: phosphotransacetylase (Pta), acetate kinase (AckA), and a lactate dehydrogenase (LdhA). The operon encoding Pta and AckA is induced in response to oxygen limitation in dependence of the anaerobic regulatory protein Anr (13). The ackA-pta locus in Escherichia coli is induced in response to starvation during aerobic conditions (31).…”
mentioning
confidence: 99%
“…Throughout the incubation period, we continuously recorded the anodic (oxidation) current as well as the charge transferred due to the oxidation of an electrochemically active component(s) at the working electrode. Periodically, we sampled to measure viability by means of counting the number of CFU on LB agar (11). We observed that the ⌬phz mutant maintained a constant viable cell number at the original 10 9 CFU/ml over 7 days, characteristic of survival but not growth (Fig.…”
mentioning
confidence: 99%